CHARACTER DEVELOPMENT AND PROFESSIONALISM TRAINING FOR TUTORS IN THE ERA OF EDUCATIONAL TRANSFORMATION - Miftahul Farid Mochamad Akhyar; Ayi Ahmad Maulana Yusup; Fitri Senny Hapsari (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2026)
This community service program aimed to enhance the character development and professionalism of tutors at Gama UI Tutoring Center Pondok Labu in response to educational transformation in the digital era. The program was initiated based on the need to strengthen pedagogical competence, reinforce professional character values, and improve adaptability to digital learning technologies. The implementation was conducted online via Zoom Meeting involving 13 active tutors. The activities included a needs assessment survey, interactive training sessions, practical workshops on using Quizizz as a digital assessment tool, and follow-up mentoring. The training emphasized integrity, responsibility, professional communication ethics, and gamification-based interactive learning strategies. The results indicated an improvement in tutors’ understanding of professionalism and character integration in teaching practices. Furthermore, tutors demonstrated enhanced skills in designing and implementing structured digital assessments using Quizizz. The program also increased tutors’ confidence in integrating technology into their teaching while fostering awareness that effective learning should focus not only on academic achievement but also on students’ character building and learning motivation. Overall, this program contributed significantly to strengthening tutors’ holistic professional capacity in the era of educational transformation.